Desenvolvimento e aplicação de método QuEChERS e UHPLC-MS/MS para determinação multirresíduo de agrotóxicos em polpa de açaí - Silva, Rafael Bel Prestes da (2024)
The North Region of Brazil, particularly the states of Pará and Amazonas, concentrates the majority of açaí production, accounting for over 85% of the national total. Considering the possibility of using pesticides on this species to maximize productivity, this study aimed to develop a comprehensive method for the multiresidue determination of pesticides in açaí pulp. A modified QuEChERS method was employed, combined with ultra-high-performance liquid chromatography coupled with tandem mass spectrometry (UHPLC-MS/MS) analysis. Various parameters of the extraction step were investigated, including different versions of QuEChERS and various sorbents for the clean-up stage, resulting in the successful validation of a method within the required parameters. The determination by UHPLC-MS/MS provided high selectivity and sensitivity. The main adjustment to the original QuEChERS method consisted of using a combination of C18 with PSA and magnesium sulfate, which were already present in the dispersive solid-phase extraction (d-SPE) cleanup step, allowing for the efficient removal of co-extractives. The method was validated for 83 compounds, showing adequate accuracy, with recoveries between 70 and 120%, and satisfactory precision with RSD  20%. The limits of quantification (LOQ) of the method ranged from 5 to 25 µg kg-1, while the detection limits varied between 1.5 and 7.5 µg kg-1. The validated method was applied to commercial açaí pulp samples from different cities in the State of Amazonas, and no pesticide residues were detected. Based on the obtained results, the proposed method proved to be rapid, efficient, and suitable for the multi-residue determination of pesticides in açaí pulp, serving as a valuable tool for routine analyses.